General geology of Kg. Gemang emphasizing on the susceptibility to shallow landslide based on shalstab model - Muhammad Fakhri Abu Bakar (2013)
Shallow landslide has become a new threat towards developing country around the globe. It is known that shallow landslide can cause a major disruption in one area and involving life. The are several known factors toward this phenomenon such as type of soil, land use, and vegetation. To avoid this situation, a model has been made to predict and to know the susceptibility of an area to experience shallow landsliding. This model results depending on the corresponding factor such as rainfall and slope gradient. Factors that triggering the shallow landslide are recognized towards the model by that, prevention or precaution step can be taken. After the model are completed, the log q/T value are compare to decide its stability.